Penerapan Asas Konsensualisme dalam Perjanjian Jual Beli Kacang Tanah di Desa Taman Kec. Jrengik Kab. Sampang: (Studi Kasus: Di Desa Taman, Kecamatan Jrengik, Kabupaten Sampang) - Aisyah Adilla; Sumriyah Sumriyah (Parlementer : Jurnal Studi Hukum dan Administrasi Publik, 2024)
An agreement according to article 1313 of the Civil Code explains that "An agreement is an act in which one or more persons bind themselves to one or more other persons". Which in this case is an agreement according to K.R.M.T Tirtodiningrat, an agreement is a legal act based on an agreement between two or more parties, which as a result of the law can be fulfilled by the provisions of the applicable law. A sale and purchase agreement is an agreement in which one party binds himself to hand over an object and the other party to pay the price of the object that has been agreed. This research is entitled "The Application of the Principle of Consensualism in the Peanut Sale and Purchase Agreement in Taman Village, Jrengik District, Sampang Regency". The purpose of this study is to find out how the principle of consensualism is applied in the peanut purchase and sale agreement in Taman Village and what are the legal consequences that will be obtained for parties who violate the principle of consensualism in the peanut purchase and sale agreement in Taman Village, Jrengik District, Sampang Regency. Thus the study uses empirical research methods. This research method is an approach that prioritizes the use of real evidence and in-depth observation as the basis for his research work. In the results of observations that have been made by researchers on the application of the principle of consensualism of peanut buying and selling agreements in Taman Village, Jrengik District, Sampang Regency, as the times go by, many residents have applied the principle of consensualism in the buying and selling process.